Design of Traffic Control System: Efficient Solutions for Traffic Control (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Traffic control has been a serious issue since human civilization. The modern world demands mobility. Cars represent the main method of mobility, but today‘s congested highways and city streets don‘t move fast, and sometimes they don‘t move at all. The India has 70 mobility on the road mode, hence the major problems created in large cities are the traffic congestion, wastage of valuable time in developed countries. For this need to solve the major problem of traffic, to achieve the strategic goal of reducing the congestion and improving the safety of the road users, main aim is to design the best traffic system that will be flexible and adoptive. Intelligent traffic systems (ITS), sometimes called intelligent transportation systems, apply communications and information technology to provide solutions to this congestion as well as other traffic control issues. The intelligent transport system (ITS) takes the first step towards meeting this challenge by providing effective, reliable and meaningful knowledge to motorists in time through signals. Problems like high traffic congestion, low transportation efficiency, low safety and endangered environment can be solved through innovative and sophisticated ways of handling latest techniques. In this paper various factors required to reduce traffic problem at various intersections are studied in details and implemented them for reducing the traffic problem form the data collected through traffic surveys at one congested points of Pune city Design of signals for one junction is carried out.